Isolation, Characterization and Cytotoxic Potential of Desmodium oojeinensis (Roxb) H. Ohashi: A Threatened Medicinal Plant - Sparsha Bandekar&, Arun B. Joshi, Anant V. Bhandarkar, Shailendra Gurav, Mythili Krishna Jeedigunta (Journal of Applied Pharmaceutical Science, 2021)
Desmodium oojeinensis, which belongs to the family Fabaceae, is an endangered plant native to the Himalayan and sub-Himalayan tract. The current work aimed to carry out physicochemical, phytochemical screening, isolation, and in vitro cytotoxic activity using MCF-7 and A-549 cell lines by using the sulforhodamine B method. The physicochemical parameters tested were found to comply with pharmacopoeial limits. The extract’s phytochemical screening revealed triterpenoids, alkaloids, anthraquinone glycosides, flavonoids, and carbohydrates. Four phytoconstituents belonging to the class of triterpenoids, viz. betulin, betulinic acid, 16-hydroxybetulin, and lupeol, were isolated from the ethanolic extract by column chromatography. The ethanolic extract showed moderate cytotoxic activity on the human lung cancer cell line A-549 at a concentration of 80 μg/ml and growth inhibition of 81.5%. The extract failed to hinder the growth of the human breast cancer cell line MCF-7.
Keywords: Desmodium oojeinensis, Fabaceae, betulin, betulinic acid,16-hydroxybetulin, lupeol.